Laminar Closure in Double-door Laminoplasty for Cervical Spondylotic Myelopathy with Nonkyphotic Alignment. Issue 15 (1st August 2021) - Sakai, Kenichiro; Hirai, Takashi; Arai, Yoshiyasu; Maehara, Hidetsugu; Torigoe, Ichiro; Inose, Hiroyuki; Tomori, Masaki; Sakaki, Kyohei; Yuasa, Masato; Matsukura, Yu; Oyaizu, Takuya; Morishita, Shingo; et al.
Abstract : Study Design: A retrospective case series. Objective: The aim of this study was to investigate the incidence and clinical features of laminar closure in patients with cervical spondylotic myelopathy (CSM) based on prospectively collected data. Summary of Background Data: Laminar closure after single open-door laminoplasty (LAMP) has been reported to result in poor clinical outcomes. However, no studies to date have examined the underlying mechanisms and frequency of laminar closure after double-door LAMP. Methods: This study prospectively enrolled 128 consecutive patients with CSM scheduled for double-door LAMP without a laminar spacer at our hospital between 2008 and 2013. Sagittal parameters including C2–7 angle, T1 slope, and cervical sagittal vertical axis (C-SVA), which is defined as the distance between the anterior margin of the external auditory canal plumb line and the posterior-cranial corner of the C7 vertebral body on x-ray, were calculated before and after the operation. Laminar angle was also measured on magnetic resonance images preoperatively and at 1 week and 1 year postoperatively. Laminar closure was defined as > 20% decrease in laminar angle at 1 year compared with that at 1 week postoperatively. The Japanese Orthopedic Association score for cervical myelopathy and the recovery rate determined from the preoperative and postoperative scores were evaluated as clinical outcomes. Results: In total, 110 patients were completely followed up for at least 1 year (follow-up rate: 85.9%). Laminar closure was observed in six cases (5.5%) at the 1-year follow-up. The recovery rate in these six cases was significantly lower than in cases without laminar closure (16.6% vs. 45.1%, respectively). Logistic regression analysis revealed age and C-SVA as significant risk factors for postoperative laminar closure. Conclusion: This study is the first to investigate the incidence of laminar closure after double-door LAMP without a laminar spacer. Laminar closure occurred exclusively in elderly patients with kyphotic deformity after LAMP. Level of Evidence: 4 Abstract : We reviewed 110 prospectively enrolled patients with cervical spondylotic myelopathy scheduled for double-door laminoplasty and measured the laminar angle on preoperative and postoperative magnetic resonance images to identify risk factors for postoperative laminar closure. The findings reveal that laminar closure occurred exclusively in elderly patients with postoperative kyphotic deformity.